Kesalehan Beragama Komunitas Hijaber di Surabaya: Dari Etis-Normatif ke Estetik-Populis - Rofhani Rofhani (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2016)
Muslimah fashion models evolve at a breakneck pace, altering not only consumption but also the perception of a person’s belief and piety. There are some wrangling overvalues, piety, and even the status of a Muslimah dressed in Islamic garb. The material and spiritual realms are fused in a dress symbol, which eventually leads to popular piety in everyday life. By integrating an ethical and aesthetic perspective into the material and spiritual realms, the existence and development of middle-class Muslimah clothing is an expression of an identity centered on the popularity of piety. By utilizing ethnographic methods such as interviews and observations of fashion trends and the Hijaber Mom Community in Indonesia, this article attempts to answer the question of whether fashion models should emphasize self-pity or follow current fashion trends. The article demonstrates how the religious practices of middle-class Muslimah have shifted. According to them, religious piety no longer occurs in a sacred space but rather in a public space. Muslimah dress evolved from ethical-normative to aesthetic-populist, resulting in the formation of popular piety and piety adapted to the development of fashion models.